Antimicrobial use quantification in adult dairy cows – Part 3 – Use measured by standardized regimens and grams on 29 dairies in the United States. Issue 1 (17th November 2020) - Schrag, Nora F. D.; Godden, Sandra M.; Apley, Michael D.; Singer, Randall S.; Lubbers, Brian V.
Abstract: This study describes antimicrobial use in terms of standardized regimens per cow year (REG/CY) and grams per cow year (GMS/CY) for 29 dairies in the United States during the years 2016 and 2017. To explore potential priorities for antimicrobial stewardship programs, these measures were stratified by both disease syndrome and antimicrobial class. Potential confounders of use measurements are discussed and challenges for measure interpretation are identified. When measured as REG/CY, the results indicate that mastitis is the disease syndrome with the greatest contribution to overall antimicrobial use. However, when GMS/CY is measured, metritis, lameness and unknown disease syndromes are also significant contributors. When use is stratified by antimicrobial class, measures of REG/CY indicate the greatest magnitude of use is the cephalosporin class. However, when measures of GMS/CY are stratified by drug class, use within the penicillin class contributes more than any other single class. These differences highlight the need for a more complete understanding of the relationship between antimicrobial use measures and their relationship to antimicrobial resistance selection pressure.